Decoding YAP dependent transcription in the liver. Issue 14 (25th July 2022) - Biagioni, Francesca; Croci, Ottavio; Sberna, Silvia; Donato, Elisa; Sabò, Arianna; Bisso, Andrea; Curti, Laura; Chiesa, Arianna; Campaner, Stefano
Abstract: The transcriptional coactivator YAP is emerging as a master regulator of cell growth. In the liver, YAP activity is linked to hepatomegaly, regeneration, dedifferentiation, and aggressive tumor growth. Here we present genomic studies to address how YAP may elicit such profound biological changes in murine models. YAP bound the genome in a TEAD-dependent manner, either at loci constitutively occupied by TEAD or by pioneering enhancers, which comprised a fraction of HNF4a/FOXA-bound embryonic enhancers active during embryonic development but silent in the adult. YAP triggered transcription on promoters by recruiting BRD4, enhancing H3K122 acetylation, and promoting RNApol2 loading and pause-release. YAP also repressed HNF4a target genes by binding to their promoters and enhancers, thus preventing RNApol2 pause-release. YAP activation led to the induction of hepatocyte proliferation, accompanied by tissue remodeling, characterized by polarized macrophages, exhausted T-lymphocytes and dedifferentiation of endothelial cells into proliferative progenitors. Overall, these analyses suggest that YAP is a master regulator of liver function that reshapes the enhancer landscape to control transcription of genes involved in metabolism, proliferation, and inflammation, subverts lineage specification programs by antagonizing HNF4a and modulating the immune infiltrate and the vascular architecture of the liver.